Optirnisation Approach to Container Chain Technology - Kolenc, Jurij; Jakomin, Livij; Trupac, Igor; Smerdu, Ivan (Promet - Traffic&Transportation, 2012)
This paper deals wiLh the selected optimisation approach tocontainer chain technology, focusing on the consignment ofcwgo from the shipper. The basic characteristics of the containerchain technology are analysed first, followed by establishingthe optimisation possibilities. A hypothesis is set assertingthat the technology of all the chain pwts has to be optimisedin order to achieve optimum functioning of the containerchain. Therefore, the container chain has been analysed as asystem consisting of subsystems of the shippe1; transpmtation,swrage and receiver (consignee). Due to similarity of the optimisationprocesses, we have only dealt with the optimisationprocess of the container chain technology from the shipper'sview, for the case of streamlining of the current condition, reconstructionand project design on new mganisation scheme.